PENGARUH PEMBERIAN KREDIT USAHA RAKYAT DAN LOKASI USAHA TERHADAP PENDAPATAN USAHA: STUDI KASUS UMKM PADA BIDANG FASHION DI KOTA SIBOLGA - Br Siringoringo, Magdalena Judika; Simanjuntak, Markus Doddy; Nababan, Tonggam Sihol; Sianipar, Gloria J.; Sari Nainggolan, Erni Yuli (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to determine the effect of the provision of People's Business Credit and Business Location on the Income of MSMEs in the fashion sector in Sibolga City. The independent variables are People's Business Credit and Business Location. While the dependent variable is Business Income. This study uses quantitative research. The type of data used in this study is primary data obtained from respondents who filled out the questionnaire, namely MSMEs in the fashion sector in Sibolga City. The sampling technique used is a purposive sampling technique with several criteria, namely: 1) MSMEs that use KUR loans, 2) MSMEs in the fashion sector. The sample of this study was 80 respondents calculated using the lemeshow formula. The tool used for this study used multiple linear regression analysis. The results of the t-test show that People's Business Credit does not have a significant effect on the Income of MSMEs in the fashion sector in Sibolga City. While Business Location has a positive and significant effect on the Income of MSMEs in the fashion sector in Sibolga City. Based on the determination coefficient test, that People's Business Credit and Business Location are able to explain their influence on the Income of MSMEs in the fashion sector in Sibolga City by 20.7%.